Desenvolvimento de molde de material cerâmico para aplicação em moldagem por injeção de materiais poliméricos - Heiderich, Danilo Carvalho (2014)
The need for speed increasing production, reducing weight and price of the product and the need for creation of complex parts made the use of polymeric materials, increasingly feasible in relation to other materials. The implementation of polymeric materials in various areas of production ensure the continued development of techniques for forming the same, with advances in technology also creates the need to increase the speed of transition between the development stages of a project as well as reducing the costs involved to achieve project deadlines and keep it commercially competitive. In view of the mechanical properties of ceramic material and its ease of forming was objective the creation of a plastic injection mold made of ceramic material. For this we performed a brief study of the main means of forming polymer and a study on the properties of ceramic and polymeric materials. Was later developed the part to be injected, and from the same, the ceramic mold that is used. After scaling the same calculations were made to adapt the project to verify its viability and the process of analysis by finite elements. These results show that the injection pressure and the necessary clamping force are below the maximum forces, supported by ceramic material, which demonstrates the viability of the ceramic mold, as an alternative to traditional metal molds.